2017
DOI: 10.3389/fmicb.2017.01935
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Gut Microbial Ecosystem with the Environment: Does Gut Health Depend on Where We Live?

Abstract: Global comparisons reveal a decrease in gut microbiota diversity attributed to Western diets, lifestyle practices such as caesarian section, antibiotic use and formula-feeding of infants, and sanitation of the living environment. While gut microbial diversity is decreasing, the prevalence of chronic inflammatory diseases such as inflammatory bowel disease, diabetes, obesity, allergies and asthma is on the rise in Westernized societies. Since the immune system development is influenced by microbial components, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 68 publications
(80 reference statements)
1
107
1
7
Order By: Relevance
“…These could then also be analysed from a One Health [139] perspective, including microbiota changes in different species and contexts, with a particular focus on obese cats and dogs [140][141][142][143]. Under this circumstance, obesity needs to be analysed in context, and we suggest as a consequence of a global change in the Anthropocene, summing events such as urbanisation, deforestation, transportation, landuse change, changes in agricultural practices, use of pesticides and loss of soil biodiversity [8,144,145].…”
Section: The Role Of Epigenetics In Explaining the Association Betweementioning
confidence: 99%
“…These could then also be analysed from a One Health [139] perspective, including microbiota changes in different species and contexts, with a particular focus on obese cats and dogs [140][141][142][143]. Under this circumstance, obesity needs to be analysed in context, and we suggest as a consequence of a global change in the Anthropocene, summing events such as urbanisation, deforestation, transportation, landuse change, changes in agricultural practices, use of pesticides and loss of soil biodiversity [8,144,145].…”
Section: The Role Of Epigenetics In Explaining the Association Betweementioning
confidence: 99%
“…Zhuang et al showed a decrease in the number of bacteria belonging to the phylum Bacteroidetes, while the number of bacteria in the phylum Firmicutes remained unchanged compared with healthy controls. These differences may be related to a number of factors, including comorbidities, ethnicity, lifestyle, and dietary preferences (Tasnim et al, 2017).…”
Section: Brain-gut-microbiota Axis and Alzheimer's Diseasementioning
confidence: 99%
“…It is common in aquaculture and hatchery settings to raise fi sh in artifi cial or semi-natural enclosures and an understanding of the fi sh gut microbiome could shed light on strategies to mitigate potential negative effects (e.g., high fi sh density, non-natural diet regime) that are well documented in these systems (Miller et al 2004 ;Araki et al 2007 ). Research on human gut microbiota has shown an overall decrease in microbial diversity in westernized society concurrent with increases in chronic infl ammatory diseases (Tasnim et al 2017 ). This has been linked to the level of "sanitation" of the host ' s environment.…”
Section: The Future Of Gut Microbiome Research In Fisheriesmentioning
confidence: 99%